Designing a Photovoltaic–Wind Energy Mix with Energy Storage for Low-Emission Hydrogen Production - Arkadiusz Małek; Agnieszka Dudziak; Andrzej Marciniak; Tomasz Słowik (Energies)
In the introduction to this article, a brief overview of the generated energy and the power produced by the photovoltaic systems with a peak power of 3 MWp and different tilt and orientation of the photovoltaic panels is given. The characteristics of the latest systems generating energy by wind turbines with a capacity of 3.45 MW are also presented. In the subsequent stages of the research, the necessity of balancing the energy in power networks powered by a mix of renewable energy sources is demonstrated. Then, a calculation algorithm is presented in the area of balancing the energy system powered by a photovoltaic–wind energy mix and feeding the low-emission hydrogen production process. It is analytically and graphically demonstrated that the process of balancing the entire system can be influenced by structural changes in the installation of the photovoltaic panels. It is proven that the tilt angle and orientation of the panels have a significant impact on the level of power generated by the photovoltaic system and, thus, on the energy mix in individual hourly intervals. Research has demonstrated that the implementation of planned design changes in the assembly of panels in a photovoltaic system allows for a reduction in the size of the energy storage system by more than 2 MWh. The authors apply actual measurement data from a specific geographical context, i.e., from the Lublin region in Poland. The calculations use both traditional statistical methods and probabilistic analysis. Balancing the generated power and the energy produced for the entire month considered in hourly intervals throughout the day is the essence of the calculations made by the authors.